Foregrounding agency in interactive-narrative based HIV interventions - Myers, Hadassah Esther (My University, 2017)
The HIV epidemic has severely affected many parts of the world, especially Sub Saharan Africa. There is clear evidence suggesting that computer-based HIV prevention interventions are efficient. Interactive‐narrative is just beginning to be explored for Technology-Based Learning. I inspect the concept of agency afforded by interactivity and participation to determine the possibilities of interactive-narrative in HIV interventions. By scrutinising three noteworthy instances of interactive-narrative based HIV interventions, I extract evaluative criteria that this format facilitates, in the way that it can preference user choice. I conclude that while platform and content may form a significant element of a successful intervention, it is the elements of navigability, identification, co-creation, immersion and transformation that direct the agency When these are interwoven successfully, interactive-narrative becomes
Keywords: HIV infections--Africa, Sub-Saharan; HIV infections--Africa, Sub-Saharan--Prevention; AIDS (Disease)--Africa, Sub-Saharan